Assessment of various risk factors associated with antineoplastic chemotherapy-induced nausea and vomiting amongst patients receiving concurrent chemoradiotherapy: A prospective study - S. Navaneetha Krishnan; Pranabandhu Das; Divya Bharathi Manikonda; Dharmika Naramsetti; Jayasree Puthalapattu; Jeswitha Velagambatti; B. V. Subramanian; Battula Pradeep (Journal of Clinical and Scientific Research, 2025)
Background: Chemotherapy-induced nausea and vomiting (CINV) is the most common side effects in the treatment of solid tumours. Sparse data are available regarding risk factors for CINV from India. Methods: We conducted this prospective observational study from January 2021 to April 2021 to find the association of risk factors such as age, gender, tobacco use, alcohol use and dietary habits with occurrence of CINV in patients with head-and-neck and uterine cervical cancer (n = 90) who were concurrently receiving chemotherapy and radiotherapy. Platinum compounds such as cisplatin (95.6%) and carboplatin (4.4%) were highly emetogenic agents that cause CINV were used as chemotherapeutic agents concurrently with radiotherapy. Results: Nausea (60%) occurred more commonly than vomiting (40%) in acute phase as well as the delayed phase. During the first cycle of chemotherapy, acute chemotherapy induced nausea was significantly associated with age <55 years compared to patients aged >55 years (95% confidence intervals [CI] 0.9869-1.107); a higher proportion of subjects who used tobacco products reported acute CINV than delayed CINV. No significant association was observed between gender, tobacco use, alcohol use, dietary habits and occurrence of CINV. Conclusions: Our observations suggest that age <55 years, constituted a risk factors for occurrence of CINV.